Children of Unknown Parents in Dar El –Amal for Orphans, Wad-Medani City, Gezira State, Sudan, 2012- 2013: Situational analysis - Hussein, Salwa Elsanousi; Yousif, Narmeen Ali; Ghebreselasie, Daniel Tekie; Ahmed, Magda Elhadi; Ali habour, Ali Babiker (مجلة الجزيرة للعلوم الصحية; مجلد 10 عدد 2 (2014), 2014)
Introduction: Orphaned children of unknown parents in poor urban communities sometimes have no adult to care for them or an adult caregiver is not able to provide adequate care due to poverty. Objectives: The objectives of this study were to assess the services provided to orphaned and vulnerable children, identify their health status and assess the care providers knowledge, attitudes and practice (KAP) towards these children in Dar El-Amal for orphans in Wad Medani city. Materials & Methods: A retrospective descriptive facility based study was designed. The records of all children (n=104) admitted to Dar El-Amal for orphans between January 2012 - January 2013 were reviewed. A cross sectional descriptive study about (the Knowledge, Attitudes, and Practices of all service providers (n=18) was conducted through questionnaires by personal interviews. The situation of orphaned children (n=15) and infrastructure of Dar El-Amal for orphans in Wad Medani city  was assessed between April-May, 2013 by observation check lists. Results: Most of the babies (70.2%) were brought to Dar Elamal at the age of less than one week. Most of the orphaned neonates (63%) belong to great Wad-Madani locality. Death rates were common among these neonates (51%) due to absence of breast feeding in early neonatal life. Sepsis was the most common cause of death (92%) among them. The vaccination service was frequently interrupted in the study group and only (6.4%) of the current studied children received BCG vaccine. Only two-third (66%) of the care providers in Dar El Amal received in service training regarding child health despite that their knowledge about childhood illnesses were poor. Conclusion and recommendations: Knowledge of care providers and provision of services to the orphan children was inadequate. The mortality rate of babies was high in their neonatal period as a result of sepsis. It is recommended that continuous in- service training of the care providers and timely vaccination of the children are priorities and adequate financial support for better care of the orphan is also mandatory.